Addressing the Needs of Sexual Partners of People Who Inject Drugs through Peer Prevention Programs in Iran - Mohammad Karamouzian; Ali Akbar Haghdoost; Hamid Sharifi (Kerman University of Medical Sciences, 2014)
Despite the fact that HIV epidemic is mainly driven by injection drug use in Iran, partners of People Who Inject Drugs (PWID) have been seriously neglected in terms of effective preventive interventions. Currently, sexual partners of PWID might have access to some harm reduction services at Voluntary Counselling and Testing (VCT) centers; however, their needs have not been effectively targeted and met. Unfortunately, the current programs implemented by the Ministry of Health have overlooked the importance of this population in the course of the HIV epidemic throughout the country. In this policy brief, we are trying to draw the health policy-makers' attention to this overlooked population and while reviewing the advantages and disadvantages of some of the readily available options on the table, come up with a recommended action to tackle this problem. Our recommended action that seems to have had promising results elsewhere in Asia would try to implement preventive interventions targeting this particular population through peer prevention programs.